2020
DOI: 10.3354/meps13365
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence that lowering the pH of concrete supports greater biodiversity on tropical and temperate seawalls

Abstract: Concrete is one of the most commonly used materials in the construction of coastal and marine infrastructure despite the well known environmental impacts which include a high carbon footprint and high alkalinity (~pH 13). There is an ongoing discussion regarding the potential positive effects of lowered concrete pH on benthic biodiversity, but this has not been investigated rigorously. Here, we designed a manipulative field experiment to test whether carbonated (lowered pH) concrete substrates support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 75 publications
2
19
1
Order By: Relevance
“…These experiments should be revisited, repeated and expanded on (e.g. Hsiung et al., 2020) to improve the evidence base for policy development. The rise of the global research network (e.g.…”
Section: Moving Forward What Can Be Done?mentioning
confidence: 99%
“…These experiments should be revisited, repeated and expanded on (e.g. Hsiung et al., 2020) to improve the evidence base for policy development. The rise of the global research network (e.g.…”
Section: Moving Forward What Can Be Done?mentioning
confidence: 99%
“…The pH was also verified using phenolphthalein indicators, which gave a pink coloration after contact with the surface of the specimens, indicating a pH higher than 9. Therefore, the surface pH measured was lower than expected (pH~13) [101,102]. This might be due to the 30 days of contact between air and mortar specimens before the start of the immersion test.…”
Section: Ph Of Mortar Surfacesmentioning
confidence: 66%
“…Cementitious materials have a very high surface alkalinity (pH~13) [101,102]. Due to this very basic pH, their constituent materials have been cited as inhibitors of the recruitment of marine biota [36].…”
Section: Ph Of Mortar Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher diversity in these alternative mixtures has tentatively been suggested to be caused by lower pH [88,99,101]. On the other hand, a recent study concluded that carbonated (lowered pH) concrete substrates did not support greater species richness and abundance, and/or alter community composition, in both temperate and tropical intertidal habitats [102]. It is possible that the use of 'natural' materials in the concrete mixture design could help increase biodiversity.…”
Section: Ecological Considerationsmentioning
confidence: 99%